2021
DOI: 10.3390/ma14185322
|View full text |Cite
|
Sign up to set email alerts
|

Quality over Quantity: How Different Dispersion Qualities of Minute Amounts of Nano-Additives Affect Material Properties in Powder Bed Fusion of Polyamide 12

Abstract: The great interest, within the fields of research and industry, in enhancing the range and functionality of polymer powders for laser powder bed fusion (LB-PBF-P) increases the need for material modifications. To exploit the full potential of the additivation method of feedstock powders with nanoparticles, the influence of nanoparticles on the LB-PBF process and the material behavior must be understood. In this study, the impact of the quantity and dispersion quality of carbon nanoparticles deposited on polyam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Moreover, an improvement of mechanical properties in parts produced from composite powders of PA12-carbon nanoplateletes or from PEEK (wet) coated with fullerene-like WS 2 and graphene nanoplatelets was reported (Yazdani et al, 2018;Chen et al, 2020). Hupfeld et al (2020c), Hupfeld et al (2020d) demonstrated that the crystallization behavior of PA12 feedstocks and their microstructure (spherulites, lamellae) can be tuned by (wet) coating with carbon nanoparticles, respectively, Ag nanoparticles produced in-situ in the liquid phase by laser-induced fragmentation of precursors (Hupfeld et al, 2020a;Sommereyns et al, 2021a;Sommereyns et al, 2021b). These authors observed improved homogeneity of the nanoparticulate coating, if the functionalization was performed by wet coating from dispersion as compared to dry particle coating.…”
Section: Figurementioning
confidence: 99%
“…Moreover, an improvement of mechanical properties in parts produced from composite powders of PA12-carbon nanoplateletes or from PEEK (wet) coated with fullerene-like WS 2 and graphene nanoplatelets was reported (Yazdani et al, 2018;Chen et al, 2020). Hupfeld et al (2020c), Hupfeld et al (2020d) demonstrated that the crystallization behavior of PA12 feedstocks and their microstructure (spherulites, lamellae) can be tuned by (wet) coating with carbon nanoparticles, respectively, Ag nanoparticles produced in-situ in the liquid phase by laser-induced fragmentation of precursors (Hupfeld et al, 2020a;Sommereyns et al, 2021a;Sommereyns et al, 2021b). These authors observed improved homogeneity of the nanoparticulate coating, if the functionalization was performed by wet coating from dispersion as compared to dry particle coating.…”
Section: Figurementioning
confidence: 99%
“…A lot of research focuses on semi-crystalline polyamide 12 (PA12). The authors of [ 16 ] were able to prove in their investigations that even small amounts of added carbon nanoparticles can significantly influence the mechanical properties without adversely changing the crystallization behavior. Metallic or ceramic additives in micro- or nanoscale embedded in a polymer matrix can be used to produce highly specialized parts even with new functionalities, like, e.g., magnetic characteristics [ 17 ].…”
mentioning
confidence: 99%